Modified small‐signal behavioral model for GaN HEMTs based on support vector regression. Issue 9 (7th June 2021) - Geng, MingQiang; Cai, Jialin; King, Justin; You, Bin; Su, Jiangtao; Liu, Jun; Sun, Lingling; Cao, Wenhui; Pan, Mian
Abstract: A novel, modified small signal behavioral modeling methodology for gallium nitride (GaN) high electron‐mobility transistors (HEMTs), based on the support vector regression (SVR) technique, is presented in this paper. Compared with the classic equivalent small‐signal circuit model, the proposed model adds an error correction technique, which is developed using SVR techniques. The proposed model maintains accuracy across a broad frequency range, from 1 GHz to 10 GHz. The verification is performed through comparisons with measured multibias S‐parameter data performed on an 8 × 125 μm GaN HEMT device with a 0.25 μm gate feature size. The modified model shows a significant improvement in S‐parameter prediction accuracy when compared with the classic equivalent circuit modeling approach.